Estimation of combining ability and heterosis for yield and its component traits for identification of promising red rice (Oryza sativa L.) hybrids developed from new WA-based CMS lines and red kernel breeding lines - V. Nagamani1, N. Shivakumar2 and T. E. Nagaraja3* (Electronic Journal of Plant Breeding, 2022)
Combining ability analysis and heterosis enables plant breeders in anticipating improvement in productivity through hybridization and selection. In this study, line × tester mating design was used to develop 42 red rice hybrids by utilizing newly developed six WA-based CMS lines and seven testers selected from red kernel breeding lines at Zonal Agricultural Research Station, V.C. Farm, Mandya during kharif, 2018. The phenotypic performance of hybrids along with parents and checks were evaluated for grain yield and yield contributing traits. Analysis of variance revealed that variance due to the line × tester was significant for almost all the characters studied. Combining ability analysis revealed the predominance of non-additive gene action for most of the characters studied. On the basis of gca effects, CMS 2 among the lines and MO-21 among testers were identified as good general combiners for most of the traits studied. High sca effects were observed in the crosses, viz., CMS-1 × ME-19, CMS-2 × IET-14757 and CMS-4 × MSN- 98 and they were also found to be the best combinations for grain yield and its component traits. The crosses CMS 5 × MSN-10-3, CMS 2 × ME-19 and CMS 5 × IET-14757 exhibited high mean grain yield and high standard heterosis over the standard commercial check KRH-4. These hybrids further need to be evaluated in multi-location trails for commercial exploitation of heterosis in red rice hybrid breeding program.